A submicron forest-like silicon surface promotes bone regeneration by regulating macrophage polarization - Sun, Guo; Shu, Tianyu; Ma, Shaoyang; Li, Meng; Qu, Zhiguo; Li, Ang (Frontiers in Bioengineering and Biotechnology, 2024)
Silicon is a major trace element in humans, and is a prospective supporting biomaterial to bone regeneration. Submicron silicon pillars, as a representative surface topography of silicon-based biomaterials, can regulate macrophage and osteoblastic cell responses. However, the design of submicron silicon pillars for promoting bone regeneration still needs to be optimized. In this study, we proposed on a submicron forest-like silicon surface (Fore) based on photoetching. The smooth silicon surface (Smo) and photoetched regular silicon pillar surface (Regu) are used as the comparison in the bone regeneration evaluation. Surface parameters are investigated using the field emission scanning electron microscope, atomic force microscope and contact angle instrument. The regulatory effect of macrophage polarization and succedent osteogenesis are studied with Raw264.7 and MC3T3-E1 cells.Finally, a mouse calvaria defect model is used for evaluating the promoting effect on bone regeneration on the three surfaces. As the result, the Fore surface can increase the expression of M2 polarized markers (CD163, CD206) and decrease the expression of inflammatory cytokines including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α). The osteoblast-related genes (Alpl, Runx2, Col1a1) in MC3T3-E1 cells and the activity of alkaline phosphatase were further up-regulated.Furthermore, the volume fraction of new bone and the thickness of trabeculae on the Fore surface were significantly increased, and the expression of RANKL was down regulated. In summary, the upregulation of macrophage M2 polarization on the Fore surface contributed to enhanced osteogenesis in vitro and accelerated bone regeneration in vivo. This study strengthens our understanding of the topography design for developing future silicon-based biomaterials.